Women’s Participation in the #FDSustainabeauty Campaign on Beauty Waste Management - Kurniasari, Dina Rizky; Pramiyanti, Alila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The growth of Indonesia's beauty industry has led to increased consumption of cosmetic products, contributing significantly to packaging waste. The #FDSustainabeauty campaign initiated by Female Daily Network aims to educate the public about sustainable beauty practices and waste management. This study analyzes the participation of women, as dominant consumers of beauty products, in the campaign across four stages: decision-making, implementation, utilization, and evaluation. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation. Results indicate that while women were not involved in decision-making, they actively participated during implementation and showed varying levels of ecological reflection in the utilization stage. However, formal mechanisms for evaluation were lacking. This study emphasizes the strategic role of visual narratives, incentives, and digital engagement in shaping women’s participation in environmental initiatives. The findings contribute to the literature on ecofeminism and participatory communication, offering practical insights for future sustainable campaigns.